Some noun paradigms and some question words - Dagny Hildegard Skaile; Joshua Karl Wilbur (Joshua Wilbur, 2008)
Linguistic documentation of the Pite Saami language (ISO693-3: sje) some noun paradigms: vágge (valley}, luakkta (bay), vuasta (cheese), båtsoj (reindeer); some of question word paradigms (“what” and “who”)